Analisis Penerapan Green Accounting Pada Pertenunan Putri Ayu - Vionavianti, Dewa Ayu Made; Karyada, I Putu Fery; Yuliantari, Ni Putu Yeni (Hita Akuntansi dan Keuangan, 2024)
The purpose of this study was to investigate whether or not Putri Ayu could benefit from using green accounting in her textile business. Research was conducted at Putri Ayu Weaving, located in Astina Field, Blahbatuh District, Gianyar Regency, Bali; the company's Financial Statements served as the study's primary research object. Observation, interviews, and careful documentation were used to compile the data for this study, which was then analysed using descriptive qualitative methods. Research shows that Putri Ayu Weaving has implemented waste management, but the company has failed to adequately disclose the associated costs. Although waste management expenses are not broken out in a discrete financial report, they are included in the cost of goods sold line of Putri Ayu Weaving's profit and loss statement. Based on the findings of the study, the government and affiliated organisations will start advising and educating businesses on the value of waste management practises, so that they can plan accordingly.